A homogeneity property for Besov spaces - António M. Caetano; Sofia Lopes; Hans Triebel (Journal of Function Spaces and Applications)
A homogeneity property for some Besov spaces Bp,qs is proved. An analogous property for some Fp,qs spaces is already known.